Hubungan Kemampuan Representasi Visual Dan Pengetahuan Faktual Mahasiswa Pada Materi Anatomi Tumbuhan - Hidayah, Nur; Bidayati Haka, Nukhbatul; Handoko, Akbar; Puspita, Laila; Reza Ningrum, Ayu; Suryani, Yani (Universitas Cokroaminoto Palopo, 2025)
During practical work, students tend to have difficulty describing the objects they are observing. This research aims to analyze the relationship between visual representation and students' factual knowledge on plant anatomy material. This type of research is descriptive correlational. The sample in this study included 33 students from a biology education study program at one of the universities in Bandung. The instruments used in this research include image analysis rubrics and tests. The image analysis rubric instrument is used to obtain data related to image representation abilities, while the test instrument is used to obtain data on students' factual knowledge. Before the correlation test is carried out, a prerequisite test is carried out first to obtain normal distribution results and linear regression. Based on the results of the correlation test, results were obtained with a significance of 0.031 < 0.05. Based on these results it can be concluded that there is a relationship between the two variables, namely between visual representation and factual knowledge. Furthermore, an r value of 0.377 was obtained, indicating that the relationship between visual representation and students' factual knowledge was categorized as low